'OF THE TEMPERAMENT OF THOSE MUSICAL INSTRUMENTS': CONSIDERING TIBERIUS CAVALLO AND THE SCIENTIFIC OBSERVATION OF MUSICAL SOUNDS IN LATE EIGHTEENTH-CENTURY LONDON. (21st March 2018) - CLARK, KATELYN
Abstract : The connection of music to scientific exploration in late Enlightenment London can be considered from various perspectives, perhaps most evidently through the binary of amateur–professional. These two realms intersected within natural philosophical observation, a practice that often served concurrently as entertainment and as study. The development of scientific instruments for the observation of various phenomena appeared in both professional and amateur contexts, contributing to technological growth and research. Natural philosopher Tiberius Cavallo (1749–1809) and his 1788 article on musical temperament ('Of the Temperament of Those Musical Instruments, in Which the Tones, Keys, or Frets, are Fixed, as in the Harpsichord, Organ, Guitar, &c') provide a captivating example of amateur interest overlapping effectively with the professional domain; as an amateur musician and professional scientist, Cavallo observed equal temperament in both mathematical and aesthetic terms. Consideration of his work promotes a more nuanced view of London as a place where scientific and musical ideas could meet and be 'instrumentalized', emphasizing the city's status as a vibrant arena for the interaction of scientific exploration, artistic endeavour and professional identities. In this sense, Cavallo's work on temperament was not merely a scientific activity; it reflected technological change during a stimulating period of scientific and musical progress in late eighteenth-century London. For example, instrument builders were actively developing ways to improve pitch control and tuning stability, as witnessed by numerous British patents for harp mechanisms, the addition of flute keys and keyboard construction.